A synthesis of 5-hydroxysedamine using hydroformylation - Bates, Roderick Wayland (2014)
A synthesis of 5-hydroxysedamine, a Sedum alkaloid, has been completed using N,O-heterocycle chemistry to establish the aminoalcohol structure, hydroformylation to form the piperidine ring and diastereoselective dihydroxylation to introduce the 5-hydroxy group.